EXPLORING THE FACTORS INFLUENCING ETHICAL CONSIDERATIONS IN REPORTING ON MIGRATION ISSUES IN LATVIAN NEWS MEDIA - Dāvidsone, Agnese; Galvanovska, Dagne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This article analyses the perceived importance of various influences on the ways in which Latvian local and national news media (print, online, TV, radio) have reported on migration issues and the process of accepting asylum seekers in Latvia during the last years. Previous studies indicate that the framing in media content depends on a large number of considerations such as general principles of ethical reporting, the established cultures inside media, and – in many cases – the individual perceptions of the “right” and “wrong” of the journalists and editors. The current study applies a qualitative approach drawing on 13 semi-structured interviews with media editors. The data analysis reveal how the perceptions of various individual, procedural and cultural influences intersect with the journalist perceptions of media roles, responsibilities and duties in a democratic society. Based on the results, suggestions are made about the opportunities of lifelong learning training development for journalists.